Cross-Platform Logistics Collaboration: The Impact of a Self-Built Delivery Service - Lanbo Li; Gang Li (Journal of Theoretical and Applied Electronic Commerce Research)
Motivated by the collaboration of a takeout platform and a crowdsourced delivery platform, we developed a stylized model to explore the interplay between the two platforms’ decisions. We captured the cross-platform network effects of the two complementary platforms, and investigated how the collaboration between the two platforms shapes the optimal prices, platform profits, and social welfare. We found that the takeout platform optimally adopts a subsidy pricing strategy when its commission rate is relatively high. In addition, when the demand-side network effect coefficient increases, the delivery platform optimally raises the shipping fee to trigger a larger supply of drivers. Furthermore, we found that the takeout platform introducing a self-logistics service reduces the subsidy intensity and raises the subsidy threshold. It also reshapes the strategic two-sided pricing to increase the network benefit when the network effect coefficient grows on one side. Specifically, as the supply-side network effect coefficient increases, instead of lowering the delivery price to increase demand and further increase the drivers’ network benefit, the takeout platform optimally raises it under certain conditions. Finally, self-logistics may benefit the takeout platform, while hurting the delivery platform, and it can increase social welfare. Our results, thus, unveil a price regime for platform collaboration and validate the effectiveness of the introduction of self-logistics by takeout platforms.